Comparative Analysis of Systemic and Tumor Microenvironment Proteomes From Children With B-Cell Acute Lymphocytic Leukemia at Diagnosis and After Induction Treatment - Broto, Geise Ellen; Corrêa, Stephany; Trigo, Fausto Celso; Santos, Everton Cruz dos; Tomiotto-Pelissier, Fernanda; Pavanelli, Wander Rogério; Silveira, Guilherme Ferreira; Abdelhay, Eliana; Panis, Carolina (Frontiers in Oncology, 2020)
Among the childhood diseases, B-cell acute lymphocytic leukemia (B-ALL) is the most frequent type of cancer. In spite of recent advances concerning disease treatment, cytotoxic chemotherapy remains as the first line of treatment in several countries, and the modifications induced by such drugs in the organism remains poorly understood. In this context, the present study provided a comparative high-throughput proteomic analysis of the cumulative changes induced by chemotherapeutic drugs used in the induction phase of B-ALL treatment in both peripheral blood (PB) and bone marrow compartment (BM) samples. To reach this goal, PB and BM plasma samples were comparatively analyzed by using label-free proteomics at two endpoints: at diagnosis (D0) and the end of the cumulative induction phase treatment (D28). Data are available via ProteomeXchange with identifier PXD021584. The resulting differentially expressed proteins were explored by bioinformatics approaches aiming to identify the main gene ontology processes, pathways and transcription factors altered by chemotherapy, as well to understand B-ALL biology in each compartment at D0. At D0, PB was characterized as a pro-inflammatory environment, with the involvement of several downregulated coagulation proteins as KNG, plasmin and plasminogen. D28 was characterized predominantly by immune response-related processes, and the super expression of the transcription factor IRF3 and transthyretin. RUNX1 was pointed out as a common transcription factor found in both D0 and D28. We chose to validate the proteins transthyretin and interferon-gamma (IFN-γ) by commercial kits, and expressed the results as PB/BM ratios. Transthyretin ratio shown augmented after induction chemotherapy, while IFN-γ was reduced at the end of the treatment. Considering that most of these proteins were not yet described in B-ALL literature, these findings added to understanding disease biology at diagnosis, and highlighted a possible role for transthyretin and IFN-γ as mechanisms related to disease resolution. Keywords: B-acute lymphocytic leukemia; chemotherapy; proteomics; induction phase; Transthyretin; interferon gamma; IRF3.